Biocontrol efficacy and possible mechanism of a broad-spectrum antagonistic yeast, Pichia kluyveri NY23, screened from peach fruit via microbiome analysis - Mengyang Xing; Qiu Long; Keyan Zhao; Yong Chen; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2027)

Highly dispersed Ni-Mo encapsulated in hollow mesoporous ZSM-5 as an efficient catalyst for tetralin conversion to light aromatics - Mengdi Wang; Limin Zhang; Haoqing Zhang; Jiaming Wu; Keyan Li; Xinwen Guo (Fuel, 2026)

Fine-grained hierarchical crop type classification from integrated hyperspectral EnMAP data and multispectral sentinel-2 time series: A large-scale dataset and dual-stream transformer method - Wenyuan Li; Shunlin Liang; Yuxiang Zhang; Liqin Liu; Keyan Chen; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Shikang Guan; Zhenwei Shi (Remote Sensing of Environment, 2026)

Structure-activity relationship and salinity-driven degradation pathway and toxicity divergence of bromophenols during advanced reduction in VUV/sulfite system - Yawei Shi; Keyan Liu; Yan Wang; Ya Sun; Zonglin Pan; Mengqi Li; Guanghui Ding (Journal of Water Process Engineering, 2026)

Morphological regulation of a flower-like hollow β-cyclodextrin covalent organic frameworks for enhanced hydrophilicity and chiral separation - Liqin Cao; Mengxue Tang; Keyan Chen; Qixuan Mu; Ruijun Li; Yibing Ji (Analytica Chimica Acta, 2026)

Distinct seasonality and trends of natural and anthropogenic wildfires in boreal forests - Cong Gao; Jinbao Li; Keyan Fang; Xu Zhang; Qi Zhang; Chunming Shi (Agricultural and Forest Meteorology, 2026)

Agglomeration under strain: Nonlinear dynamics of urban functional conflicts - Hongbo Zhao; Zeting Jia; Wenhui Yue; Yansui Liu; Qiyang Liu; Li Yue; Shaozhen Cao; Yilin Ma; Keyan Lu (Sustainable Cities and Society, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Three-Dimensional Mineral Prospectivity Mapping by a Gradient Boosting-Based Integrated Learning Method with Data Representation Adaptability: A Case Study of the Haopinggou Gold Polymetallic Deposit, China - Mingjing Fan; Keyan Xiao; Li Sun; Nan Li; Yang Xu; Wenjie Li (Natural Resources Research, 2026)

A multi-source precipitation blending method combining hydrological model-guided precipitation adjustment and double transfer learning-based data merging - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Jiahua Wei; Yuefei Huang; Shenglong Gu; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2026)

Microbial adaptation and environmental co-selection drive antimicrobial resistance risk in agricultural ditches, evidence from the multilevel ditch-river continuum - Xiangyao Wu; Yulin Qi; Lingchen Meng; Keyan Li; Chao Ma; Dietrich A. Volmer; Chunmei Chen; Peizhe Sun; Pingqing Fu; Zhifeng Yan (Journal of Hazardous Materials, 2026)

Identification of new virulence factors in Penicillium expansum via comparative transcriptomic analysis of three Penicillium species - Ting Liu; Keyan Zhao; Mengyang Xing; Yong Chen; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Spatiotemporal prediction and differentiated governance of coal mining subsidence in the desert-loess transition region - Pengyu Li; Keyan Guo; Yaokun Fu; Gensheng Li (Journal of Cleaner Production, 2026)

Contrasting cambial phenology and xylogenesis of southern and northern tree species in a boreal–temperate ecotone - Junzhou Zhang; Yiping Zhang; Min Li; Junliang Xu; Tessa Mandra; Keyan Jiang; David Orwig; Neil Pederson (Forest Ecology and Management, 2026)

Boundary-based random forest leveling of multi-map geochemical data: A case study of the Baiyinchagan-Maodeng Area, Inner Mongolia - Rui Tang; Cheng Li; Keyan Xiao (Journal of Geochemical Exploration, 2026)

GTF: A New Interpretable Graph Neural Network for Geochemical Anomaly Detection in Mineral Prospectivity Mapping - Zhengbo Yu; Binbin Li; Fan Zhang; Jiangwei You; Baizhi Li; Zhe Chen; Shuai Zhang; Keyan Xiao (Natural Resources Research, 2026)

AgriFM: A multi-source temporal remote sensing foundation model for Agriculture mapping - Wenyuan Li; Shunlin Liang; Keyan Chen; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Yuxiang Zhang; Shikang Guan; Husheng Fang; Zhenwei Shi (Remote Sensing of Environment, 2026)

Single-tube duplex isothermal amplification assay for rapid detection of pistachio and cashew allergens - Ruifeng Mao; Yuwen Zhou; Xinru Zhan; Miqi Tan; Yue Sun; Yuanmeng Dong; Keyan Yuan; Yingying Chen; Wei Wang; Dengchao Li; Enjie Diao (Food Control, 2026)

An integrated framework combining deep learning and multicriteria decision-making for SDG-oriented urban low-carbon transition capacity assessment - Wentao Wang; Dezhi Li; Keyan Liu; Yongheng Zhao; Huan Zhou; Shenghua Zhou (Environmental Impact Assessment Review, 2026)

Tree-ring δ18O reveals a consistent decrease in April precipitation in southeastern China since the 1950s and its linkage to global climate phenomena - Fang Wang; Guoliang Lei; Chotika Muangsong; Binggui Cai; Miaofa Li; Keyan Fang; Nathsuda Pumijumnong; Rattanakorn Chatwatthana; Shankar Panthi (Global and Planetary Change, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

Drip irrigation combined with organic fertilizers improves crop N uptake and yield by reducing soil salinity and N loss in saline–alkali sunflower farmlands - Min Hu; Yue Li; Zhijun Chen; Keyan Lv; Yunwu Xiong; Guanhua Huang (Soil and Tillage Research, 2026)

A Dual-Channel Iterative Method Integrating Semi-supervised Self-Training and Interpretable Deep Learning Models for Mineral Prospectivity Prediction - Shitao Yin; Nan Li; Keyan Xiao; Xianglong Song; Xingjie Wang (Natural Resources Research, 2025)

Innovative for farmland reclamation: Optimizing earthwork allocation and elevation in mining-induced subsidence - Zhuo Wang; Gensheng Li; Junjiang Liu; Keyan Guo; Honglin Liu; Tenghao Wang; Jinmao Ju; Junhui Zhang (Journal of Environmental Management, 2025)

Organic amendments promote sunflower nutrient uptake by recruiting stable beneficial microbiomes in saline–alkali farmland - Min Hu; Yue Li; Zhijun Chen; Keyan Lv; Yunwu Xiong; Guanhua Huang (Plant and Soil, 2025)

A runoff prediction approach based on machine learning, ensemble forecasting and error correction: A case study of source area of Yellow River - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Baiyinbaoligao; Jiahua Wei; Jie Gao; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2025)

Innovation for mine reclamation: Improving the reclamation efficiency and cropland rate in mining subsidence areas - Gensheng Li; Keyan Guo; Zhenqi Hu; Zhuo Wang; Wenjuan Wang; Yaokun Fu; Jinmao Ju; Junhui Zhang (Journal of Cleaner Production, 2025)

Multidecadal modulation of multi-year El Niño events over the past millennium - Shuheng Lin; Keyan Fang; Hao Wu; Hanjie Fan; Feifei Zhou; Jinbao Li; Kaiqiang Deng; Hans W. Linderholm; Song Yang (Science China Earth Sciences, 2025)

Overexpression of long non‑coding RNA H19 enhances cell viability and inhibits apoptosis in recurrent spontaneous abortion by targeting the miR-29a-3p/SOCS3 axis - Zhengli Qian; Keyan Luo; Mingzhe Zhang; Dejing Wang; Yu Hu; Qinghan Li (In Vitro Cellular & Developmental Biology - Animal, 2025)

The first temperature reconstruction based on tree-ring blue intensity in the Qinling Mountains - Mei Xie; Qiufang Cai; Yu Liu; Keyan Fang; Qiuyue Zhou; Meng Ren; Kebayier Meng; Qiang Li; Changfeng Sun; Huiming Song; Dan Chen; Yufei Chen (Dendrochronologia, 2025)

Ferroelectric-coupled MXene/BaTiO3 nanocomposite empowering flexible triboelectric nanogenerators for deep learning-enhanced human-machine health monitoring - Haoyu Yuan; Ziran Wang; Keyan Yuan; Ke Li; Chen Wang; Luyang Zhang; Zaiyu Zhang; Chaqi Gai; Chengpeng Zhang; Guoliang Lu; Zhongjing Ren; Haipeng Wang; et al. (Chemical Engineering Journal, 2025)

Framework for short-term hydropower cascade–station–unit integrated multi-objective scheduling: Considering unit safety and economic efficiency - Jingwei Huang; Hui Qin; Xu Yang; Keyan Shen; Huaming Yao; Xinyu Chang; Gaoge Li; Yuan Gao (Journal of Hydrology, 2025)

The negative effects of competition on tree resilience weakened as drought severity intensified - Xinyu Han; Lushuang Gao; Xianliang Zhang; Keyan Fang; Sijie Li; Keda Cui; Mengzhao Guo; Xiuhai Zhao (Agricultural and Forest Meteorology, 2025)

The biodegradation pathway of HBCDs in the enriched microbial community - Bing Zhang; Wenqi Luo; Yongjin Liu; Haonan Chen; Tiantian Pan; Baole Wang; Keyan Li; Huaqing Jia; Shirou Zhou; Shanshan Meng; Xueying Ye; Tao Peng; et al. (International Biodeterioration & Biodegradation, 2025)

Structure and dynamics of stationary fronts in an angled river plume - Keyan Liu; Jiaxue Wu; Huan Liu; Xiangyu Li; Zhenkun Lin; Leiping Ye (Estuarine, Coastal and Shelf Science, 2025)

A scalable photovoltaic-type photoelectrotrophic denitrification reactor for selective conversion nitrate to nitrogen via isolating reactive oxygen species - Man Chen; Keyan Chen; Yang Li; Youming Diao; Yixi Li; Raymond Jianxiong Zeng; Shungui Zhou (Chemical Engineering Journal, 2025)

Epidermal growth factor receptor targeted photodynamic degrader to activate breast cancer immunity by intensifying immunogenic cell death and downregulating PD-L1 - Keyan Zhang; Junmei Nie; Yeyang Wu; Zhenming Lu; Ziwen Qiu; Zhuofeng Li; Yingtao Zhong; Hong Cheng (Chemical Engineering Journal, 2025)

Representing the Uncertainty of a 3D Geological Model via Global Optimum Truth Discovery Technology - Nan Li; Keyan Xiao; Shitao Yin; Cangbai Li; Xianglong Song; Wenkai Chu; Weihua Hua; Rui Cao (Natural Resources Research, 2025)

Insights into the differences in meat quality among different sheep breeds in the Qilian Mountains from the perspective of metabolomics and transcriptomics - Keyan Ma; Juanjuan Song; Dengpan Li; Zilong Liu; Chunhui Wang; Taotao Li; Youji Ma (Food Bioscience, 2025)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Ultra-low silica zeolite TON: Facile synthesis and efficient catalysis in n-dodecane hydroisomerization - Haopeng Su; Qiuming Zhou; Keyan Jin; Qiang Li; Yufei Wang; Weibin Fan; Jia-Nan Zhang; Wenfu Yan (Fuel, 2024)

Study on exploring the extraction of geological elements from 3D geological models within the constraints of geological knowledge - Guangjun Ji; Zizhao Cai; Yan Lu; Jixiang Zhu; Keyan Xiao; Li Sun (Computers & Geosciences, 2024)

Deciphering the transfer of hydroclimate signals to tree-ring δ18O using a proxy system model in East Asia's Meiyu region - Yesi Zhao; Huayu Lu; Keyan Fang; Peng Zhang; Deliang Chen; Achim Bräuning; Jussi Grießinger; Bao Yang; Chenghong Liang; Hongyan Zhang; Yiqian Sun; Qing Jin; et al. (Chemical Geology, 2024)

Reactive transport numerical modeling of intermediate sulfidation epithermal deposit: A case study of Haopinggou Ag-Au-Pb-Zn deposit, Henan province, China - Cheng Chang; Keyan Xiao; Guanhong Feng; Li Sun; Junsheng Yang (Journal of Geochemical Exploration, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

Examining the effect of sample size on the estimation of low-frequency signals in tree-ring chronologies - Hao Wu; Keyan Fang; Xinyan Li (Dendrochronologia, 2024)

Deep multimodal fusion for 3D mineral prospectivity modeling: Integration of geological models and simulation data via canonical-correlated joint fusion networks - Yang Zheng; Hao Deng; Jingjie Wu; Shaofeng Xie; Xinyue Li; Yudong Chen; Nan Li; Keyan Xiao; Norbert Pfeifer; Xiancheng Mao (Computers & Geosciences, 2024)

Influence of different tectonic settings on fracture formation and fluid flow around upper-crustal magmatic intrusion: insights from numerical modelling - Cheng Chang; Keyan Xiao; Gang Luo; Li Sun (Earth Science Informatics, 2024)
Large porphyry Cu and epithermal Au deposits tend to form in distinct tectonic, porphyry and high-sulfidation epithermal deposits in compressional settings, and low-sulfidation epithermal deposits in extensional settings. Given that the analysis of the shallow metallogenic dynamic processes at the upper-crust scale is insufficient, especially the ore-bearing fracture formation and fluid-focusing mechanism around the mineralizing magmatic intrusion under different tectonic backgrounds, we aimed to study how tectonic settings influence fracture formation and fluid hydrodynamics in and around a hot intrusion. We developed a finite element model coupling thermal-hydrological-mechanical processes to simulate the fracture formation, evolution of fluid velocities, and accumulation of water-rock interactions. The model results show that tectonic compression increases the degree of fracturing, hydrothermal fluid velocities, and water-rock interaction within and laterally around the intrusion; tectonic extension enhances fracturing, hydrothermal fluid velocities, and water-rock interaction at shallow depth. These results confirm that tectonic compression may promote the formation of porphyry Cu deposits, while tectonic extension may promote the formation of shallow hydrothermal deposits. Our model explains the effects of tectonic activity on fracture formation and fluid flow around hot magmatic intrusions in upper crust and deepens our understanding of the relationship between tectonic activity and deposit formation there.

RNAi-mediated plant sterol modification to control insect herbivore pests: insights from Arabidopsis and the diamondback moth - Ivy W. Chen; Robert J. Grebenok; Cheng Zhao; Li He; Jiaxin Lei; Rui Ji; Nicolo Hernandez; Joshua S. Yuan; Hisashi Koiwa; Spencer T. Behmer; Keyan Zhu-Salzman (Journal of Pest Science, 2024)

An Uncertainty Analysis Method Based on a Globally Optimal Truth Discovery Model for Mineral Prospectivity Mapping - Nan Li; Shitao Yin; Cangbai Li; Yishi Wang; Keyan Xiao; Rui Cao; Weihua Hua; Wenkai Chu; Xianglong Song; Cheng Li (Mathematical Geosciences, 2024)

Comparing multiple machine learning models to investigate the relationship between urban morphology and PM2.5 based on mobile monitoring - Jianfeng Zhang; Yang Wan; Meng Tian; Hao Li; Keyan Chen; Xuesong Xu; Lei Yuan (Building and Environment, 2024)

Conjugating remotely sensed data assimilation and model-assisted estimation for efficient multivariate forest inventory - Zhengyang Hou; Keyan Yuan; Göran Ståhl; Ronald E. McRoberts; Annika Kangas; Hao Tang; Jingyi Jiang; Jinghui Meng; Qing Xu; Zengyuan Li (Remote Sensing of Environment, 2023)

Growth responses to climate warming and their physiological mechanisms differ between mature and young larch trees in a boreal permafrost region - Xi Qi; Paolo Cherubini; Kerstin Treydte; Mai-He Li; Zhengfang Wu; Hong S. He; Haibo Du; Keyan Fang; Matthias Saurer (Agricultural and Forest Meteorology, 2023)

A novel method for efficient recovery of ilmenite by high gradient magnetic separation coupling with magnetic fluid - Xiayu Zheng; Li Du; Shuangjia Li; Zihang Jing; Dongfang Lu; Keyan Jia; Kadir Cadiere; Bingyao Peng; Yuhua Wang (Minerals Engineering, 2023)

Revisiting the natural resources-financial development nexus in China: The importance of economic policy uncertainty - Yizhong Sun; Keyan Jin; Deyong Wang; Qingyang Wu; Zhezhou Li (Resources Policy, 2023)

Overexpression of Sly-miR167a delayed postharvest chilling injury of tomato fruit under low temperature storage - Lei Li; Xuanqi Wang; Jieyu Lv; Wenhui Duan; Taishan Huang; Keyan Zhao; Lanhuan Meng; Hongmiao Song; Qing Wang; Xiangbin Xu; Jiangkuo Li (Postharvest Biology and Technology, 2023)

Detection and quantification of cotton trichomes by deep learning algorithm - Keyan Luo; Yu Jin; Shuhan Wen; Yicheng Li; Junkang Rong; Mingquan Ding (Computers and Electronics in Agriculture, 2023)

ZYY-B-2, a novel ALK inhibitor, overcomes resistance to ceritinib by inhibiting P-gp function and induces apoptosis through mitochondrial pathway in ceritinib-resistant H2228 cells - Ying Gao; Tong Liu; Jingang Liu; Yuying Yang; Keyan Sun; Zengqiang Li; Xin Zhai; Daiying Zuo (Chemico-Biological Interactions, 2023)

Weakened western Pacific teleconnection pattern caused a decrease in spring persistent rainfall in north of 26°N over Southeast China - Yao Chen; Chongqing Wang; Feifei Zhou; Shixiong Jiang; Xi Li; Sunxian Weng; Xinyuan Wan; Rongyang Xiao; Qiang Liu; Keyan Fang (International Journal of Climatology, 2023)
The spring persistent rainfall (SPR) is a unique synoptic and climatic phenomenon before the onset of the Asian summer monsoon over Southeast China (SEC). The warming climate has caused notable interdecadal changes of various climate systems, such as the Asian summer monsoon. However, it is still unclear whether there is a regime shift within the SPR band. To fill this knowledge gap, the boreal spring (March–May) rainfall data across SEC from the Climate Research Unit TS 4.05 are used herein to reveal its spatio‐temporal variations for 1951–2019 with the empirical orthogonal function (EOF) analysis. The EOF1 pattern exhibits a spatial monotonic variability of the SPR over SEC, which is jointly impacted by the El Niño‐Southern Oscillation and the Arctic Oscillation. The EOF2 pattern, a south–north dipole pattern, highlights a marked decrease (increase) of the SPR approximately to north (south) of the 26°N. We find that the decrease in the northern SPR band is closely modulated by western Pacific teleconnection pattern (WPP). Recent weakening WPP is coincident with a decline of the East Asian subtropical jet over this area, causing anomalous descending motions and thus accounts for persistent decline of the SPR over north of 26°N.

Dexmedetomidine alleviates cerebral ischemia-reperfusion injury via inhibiting autophagy through PI3K/Akt/mTOR pathway - Jianli Li; Keyan Wang; Meinv Liu; Jinhua He; Huanhuan Zhang; Huan Liu (Journal of Molecular Histology, 2023)

Rapid expansion of wetlands on the Central Tibetan Plateau by global warming and El Niño - Yang Li; Zhengyang Hou; Liqiang Zhang; Changqing Song; Shilong Piao; Jintai Lin; Shushi Peng; Keyan Fang; Jing Yang; Ying Qu; Yuebin Wang; Jingwen Li; et al. (Science Bulletin, 2023)

In-situ construction of BiOBr/Bi2WO6 S-scheme heterojunction nanoflowers for highly efficient CO2 photoreduction: Regulation of morphology and surface oxygen vacancy - Jiaming Wu; Keyan Li; Siyu Yang; Chunshan Song; Xinwen Guo (Chemical Engineering Journal, 2023)

Metabolism balance regulation for squalene production by disturbing triglyceride (TAG) synthesis in Schizochytrium sp. - Ran Duan; Xueshan Pan; Keyan Li; Qinghua Yang; Xiaowen Cui; Yayun Zheng; Yinghua Lu; Chuanyi Yao; Xueping Ling (Algal Research, 2023)

Mineral Prospectivity Mapping based on Isolation Forest and Random Forest: Implication for the Existence of Spatial Signature of Mineralization in Outliers - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Hantao Wei; Fan Yang; Zhenghui Chen; Nan Li; Jie Xiang (Natural Resources Research, 2022)

The intra-annual intrinsic water use efficiency dynamics based on an improved model - Xiaojin Bing; Keyan Fang; Xiaoying Gong; Wenzhi Wang; Chenxi Xu; Maihe Li; Chaoyue Ruan; Weiting Ma; Yingjun Li; Feifei Zhou (Climatic Change, 2022)

Geochemically Constrained Prospectivity Mapping Aided by Unsupervised Cluster Analysis - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Zhenghui Chen; Nan Li; Hantao Wei; Jie Xiang; Li Sun; Yang Xu (Natural Resources Research, 2021)

Uncertainty Visualisation of a 3D Geological Geometry Model and Its Application in GIS-Based Mineral Resource Assessment: A Case Study in Huayuan District, Northwestern Hunan Province, China - Nan Li; Cangbai Li; Wenkai Chu; Keyan Xiao; Weihan Tao; Xianglong Song; Rui Cao; Yang Xu; Mingjing Fan (Journal of Earth Science, 2021)

Biodegradable chitosan-ethylene glycol hydrogel effectively adsorbs nitrate in water - Changhong Chen; Yiwei Guo; Li Long; Keyan Chen; Xiaolan Hu; Yingwen Xue (Environmental Science and Pollution Research, 2020)

Reinvestigation of the substrate specificity of a reverse prenyltransferase NotF from Aspergillus sp. MF297-2 - Keyan Yang; Shu-Ming Li; Xiaoqing Liu; Aili Fan (Archives of Microbiology, 2020)

3D Mineral Prospectivity Mapping with Random Forests: A Case Study of Tongling, Anhui, China - Jie Xiang; Keyan Xiao; Emmanuel John M. Carranza; Jianping Chen; Shi Li (Natural Resources Research, 2020)

3D Geological Modeling for Mineral System Approach to GIS-Based Prospectivity Analysis: Case Study of an MVT Pb–Zn Deposit - Nan Li; Xianglong Song; Cangbai Li; Keyan Xiao; Shengmiao Li; Haiyan Chen (Natural Resources Research, 2019)

East Asian Summer Monsoon moisture sustains summer relative humidity in the southwestern Gobi Desert, China: evidence from δ18O of tree rings - Qiang Li; Yu Liu; Takeshi Nakatsuka; Keyan Fang; Huiming Song; Ruoshi Liu; Changfeng Sun; Gang Li; Ke Wang (Climate Dynamics, 2019)

Interdecadal modulation of the Atlantic Multi-decadal Oscillation (AMO) on southwest China’s temperature over the past 250 years - Keyan Fang; Zhengtang Guo; Deliang Chen; Lei Wang; Zhipeng Dong; Feifei Zhou; Yan Zhao; Jinbao Li; Yingjun Li; Xinguang Cao (Climate Dynamics, 2019)

Intensified variability of the El Niño–Southern Oscillation enhances its modulations on tree growths in southeastern China over the past 218 years - Lei Wang; Keyan Fang; Dai Chen; Zhipeng Dong; Feifei Zhou; Yingjun Li; Peng Zhang; Tinghai Ou; Guoyang Guo; Xinguang Cao; Mingtong Yu (International Journal of Climatology, 2018)
Lack of long‐term tree‐ring records in the core regions of the Asian summer monsoon in southeastern China limits our ability of evaluating the current climate change in a historical context. In this study, we developed the first 218‐year tree‐ring chronology (1798–2015) of Pinus massoniana in Zhangping area, Fujian Province, humid subtropical China. This chronology is positively correlated with winter–spring (January–March) temperature ( r = 0.359, p r = 0.351, p r = 0.30, N = 66) matches closely with the ENSO variability during 1950–2015. The modulations of the ENSO on regional tree growth have been the most conspicuous since the 1950s, which corresponds to its enhanced inter‐annual variability. The extreme growth anomalies match quite well with the extreme years of the moisture‐sensitive chronologies. The dry epoch from 1935 to 1958 is the most severe long‐lasting drought in our tree rings, which is a widely distributed pattern in southeastern China and is likely modulated by the La Niña‐like modes in that period.

Drought variation of western Chinese Loess Plateau since 1568 and its linkages with droughts in western North America - Keyan Fang; Zhengtang Guo; Deliang Chen; Hans W. Linderholm; Jinbao Li; Feifei Zhou; Guoyang Guo; Zhipeng Dong; Yingjun Li (Climate Dynamics, 2017)

Abrupt vegetation shifts caused by gradual climate changes in central Asia during the Holocene - Yan Zhao; YaoLiang Liu; ZhengTang Guo; KeYan Fang; Quan Li; XianYong Cao (Science China Earth Sciences, 2017)

Climate–growth relationships of Schrenk spruce (Picea schrenkiana) along an altitudinal gradient in the western Tianshan mountains, northwest China - Yuxia Huo; Xiaohua Gou; Wenhuo Liu; Jinbao Li; Fen Zhang; Keyan Fang (Trees, 2017)

Interdecadal moisture patterns and teleconnections in Monsoonal Asia over the past seven centuries - Feifei Zhou; Keyan Fang; Fen Zhang; Yingjun Li (International Journal of Climatology, 2017)
Interdecadal (10‐ to 100‐year oscillation) moisture variations over the Monsoonal Asia ( MA ) is highly variable across regions and time, which are relatively less understood due to the shortness of the instrumental data of a few decades. In this study, comprehensive investigations on the spatiotemporal distributions of the interdecadal moisture variations over MA as well as their evolution from prior to the industrial era were conducted utilizing the tree‐ring based drought reconstructions, i.e. the Monsoonal Asia Drought Atlas. Nine interdecadal moisture patterns in MA are identified using the self‐organizing map based on the ensemble empirical mode decomposition. To further investigate these interdecadal moisture patterns, we aggregated the selected nine nodes into four patterns using a hierarchical clustering approach. Among them, Pattern 1 stands for a teleconnection between the Northeast MA and the Indian Peninsula, and Pattern 2 represents a dipole pattern between the Southern and Northern MA . We find that Pattern 1 may be linked with the dynamics of the Antarctic Oscillation that can modulate the strength of the Asian summer monsoon through meridional teleconnections. Pattern 2 is mainly driven by the elevated El Niño‐Southern Oscillation variance and the zonal ‘Silk Road Pattern’ to bridge this interdecadal modulation.

Moisture increase in response to high-altitude warming evidenced by tree-rings on the southeastern Tibetan Plateau - Jinbao Li; Jiangfeng Shi; David D. Zhang; Bao Yang; Keyan Fang; Pak Hong Yue (Climate Dynamics, 2017)

Nonlinear characteristics of hydroclimate variability in the mid-latitude Asia over the past seven centuries - Feifei Zhou; Keyan Fang; Yingjun Li; Qiuyan Chen; Dan Chen (Theoretical and Applied Climatology, 2016)

Response of Pinus taiwanensis growth to climate changes at its southern limit of Daiyun Mountain, mainland China Fujian Province - Dan Chen; KeYan Fang; YingJun Li; ZhiPeng Dong; Yu Zhang; FeiFei Zhou (Science China Earth Sciences, 2016)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Pea aphid promotes amino acid metabolism both in M edicago truncatula and bacteriocytes to favor aphid population growth under elevated CO 2 - Huijuan Guo; Yucheng Sun; Yuefei Li; Bin Tong; Marvin Harris; Keyan Zhu‐Salzman; Feng Ge (Global Change Biology, 2013)
Rising atmospheric CO 2 levels can dilute the nitrogen ( N ) resource in plant tissue, which is disadvantageous to many herbivorous insects. Aphids appear to be an exception that warrants further study. The effects of elevated CO 2 (750 ppm vs. 390 ppm) were evaluated on N assimilation and transamination by two M edicago truncatula genotypes, a N‐fixing‐deficient mutant ( dnf1 ) and its wild‐type control (Jemalong), with and without pea aphid ( Acyrthosiphon pisum ) infestation. Elevated CO 2 increased population abundance and feeding efficiency of aphids fed on Jemalong, but reduced those on dnf1 . Without aphid infestation, elevated CO 2 increased photosynthetic rate, chlorophyll content, nodule number, biomass, and pod number for Jemalong, but only increased pod number and chlorophyll content for dnf1 . Furthermore, aphid infested Jemalong plants had enhanced activities of N assimilation‐related enzymes (glutamine synthetase, Glutamate synthase) and transamination‐related enzymes (glutamate oxalate transaminase, glutamine phenylpyruvate transaminase), which presumably increased amino acid concentration in leaves and phloem sap under elevated CO 2 . In contrast, aphid infested dnf1 plants had decreased activities of N assimilation‐related enzymes and transmination‐related enzymes and amino acid concentrations under elevated CO 2 . Furthermore, elevated CO 2 up‐regulated expression of genes relevant to amino acid metabolism in bacteriocytes of aphids associated with Jemalong, but down‐regulated those associated with dnf1 . Our results suggest that pea aphids actively elicit host responses that promote amino acid metabolism in both the host plant and in its bacteriocytes to favor the population growth of the aphid under elevated CO 2 .

Spatiotemporal variability of tree growth and its association with climate over Northwest China - Keyan Fang; Xiaohua Gou; Fahu Chen; Edward Cook; Jinbao Li; Yingjun Li (Trees, 2012)

Precipitation variability during the past 400 years in the Xiaolong Mountain (central China) inferred from tree rings - Keyan Fang; Xiaohua Gou; Fahu Chen; David Frank; Changzhi Liu; Jinbao Li; Miklos Kazmer (Climate Dynamics, 2012)

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Spatial drought reconstructions for central High Asia based on tree rings - Keyan Fang; Nicole Davi; Xiaohua Gou; Fahu Chen; Edward Cook; Jinbao Li; Rosanne D’Arrigo (Climate Dynamics, 2010)

Reconstructed droughts for the southeastern Tibetan Plateau over the past 568 years and its linkages to the Pacific and Atlantic Ocean climate variability - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Nicole Davi (Climate Dynamics, 2010)

Tree‐ring based drought reconstruction for the Guiqing Mountain (China): linkages to the Indian and Pacific Oceans - Keyan Fang; Xiaohua Gou; Fahu Chen; Rosanne D'Arrigo; Jinbao Li (International Journal of Climatology, 2010)
We have reconstructed the Palmer Drought Severity Index (PDSI) from 1618 to 2005 for the Guiqing Mountain area, north central China, using tree rings of Pinus tabulaeformis . The reconstruction explains 49% of the actual PDSI variance during the common period 1951–2005. The PDSI reconstruction is representative of moisture conditions over a large area to the south and east of the sampling site, the core area for the 1997 severe drought. It shows slightly different variations when compared to other available PDSI reconstructions north and west of the sampling sites. The drought epoch since 1994 is most severe for our study region, with least intensity for the Helan Mountain area. The drought in 1997 was centered in the Guiqing Mountain area, and appears to be the most extreme drought event over the length of reconstruction. Significant spectral peaks are identified at 2.1, 2.3, 2.5, 3.2, 3.6, 42.7 and 53.8 years. Our reconstructed droughts are significantly correlated with sea surface temperature in the northern Indian Ocean, western equatorial Pacific Ocean, eastern equatorial Pacific Ocean, Eastern China Sea and Sea of Japan. The linkages to the Indian and Pacific Oceans suggest the connection of regional moisture variations to the Asian monsoon circulations. Copyright © 2009 Royal Meteorological Society

Response of regional tree-line forests to climate change: evidence from the northeastern Tibetan Plateau - Keyan Fang; Xiaohua Gou; Fahu Chen; Jianfeng Peng; Rosanne D’Arrigo; William Wright; Mai-He Li (Trees, 2009)